The Coronation of the Early Sasanians, Ctesiphon, and the Great Diadem of Paikuli. - Shenkar, Michael (Journal of Persianate Studies, 2019)
The article discusses the venue and the nature of the coronation ceremony of the Sasanian kings in the third century. It is argued that the coronation of the early Sasanians was a continuation of a Hellenistic ceremony, which was essentially the act of binding a diadem around one's head. It seems that the common practice was for the king to bind the diadem himself in the presence of a select circle of courtiers or only in the presence of the gods. Furthermore, the article will demonstrate that Ctesiphon was neither the "capital" nor even the most important residence of the early Sasanians and no ceremony of coronation took place there in the third century.